The The Potential of Pantai Indah Kemangi for Marine Tourism in Kendal - Hardiat Dani Satria (Politeknik Pariwisata Makassar, 2024)
Background: Kendal Regency has significant potential in the tourism sector, particularly in marine tourism. One of the iconic beaches is Pantai Indah Kemangi, located in Jungsemi Village, Kangkung District. Pantai Indah Kemangi needs to be developed to maximize its potential as a tourism industry hub. Objective: The purpose of this research is to analyze the potential of Pantai Indah Kemangi as a marine tourism destination in Kendal. This study identifies the factors that support the development of this beach as a potential tourist destination. Method: This research employs a descriptive qualitative research method, with data collected through interviews, secondary data analysis, and field observations. Result: Pantai Indah Kemangi has great potential to develop as a leading marine tourism destination in the North Coast region. This area can stimulate local economic growth, especially with the development of Micro, Small, and Medium Enterprises (MSMEs) in Jungsemi Village. The local government has also undertaken reforestation around the beach by planting sea pines, emphasizing environmental sustainability and the coastal ecosystem. Discussion: Pantai Indah Kemangi has significant potential to become an iconic marine tourism destination in the North Coast (Pantura) area. However, to optimize this potential, the road access needs to be revitalized to accommodate larger vehicles, and adequate lighting should be added. Conclusion: Pantai Indah Kemangi has made a substantial contribution to the development of marine tourism in Kendal, attracting both local and out-of-town tourists. Therefore, to ensure the continued growth of this tourist area, more effective promotion and improved services that do not disadvantage consumers are necessary